2019
DOI: 10.1136/annrheumdis-2019-216040
|View full text |Cite|
|
Sign up to set email alerts
|

Emergent high fatality lung disease in systemic juvenile arthritis

Abstract: ObjectiveTo investigate the characteristics and risk factors of a novel parenchymal lung disease (LD), increasingly detected in systemic juvenile idiopathic arthritis (sJIA).MethodsIn a multicentre retrospective study, 61 cases were investigated using physician-reported clinical information and centralised analyses of radiological, pathological and genetic data.ResultsLD was associated with distinctive features, including acute erythematous clubbing and a high frequency of anaphylactic reactions to the interle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
97
0
24

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(143 citation statements)
references
References 82 publications
3
97
0
24
Order By: Relevance
“…Intriguingly, almost 50% of patients had experienced an adverse reaction to a biologic drug, most characteristically an allergic-type reaction to tocilizumab, an otherwise quite uncommon event. These findings are echoed in the still-unpublished larger series, which includes 9 patients who were also described in the study by Schulert and colleagues, although in the larger series an extrapolated mortality of >50% at 5 years has been observed, as well as features such as lymphopenia and a striking overrepresentation of patients with trisomy 21 (8). Considering only referrals within the Cincinnati catchment area, Schulert et al provide the first estimate of the prevalence of LD in systemic JIA patients, 5 of 74 (or almost 7%), making SJIA-LD a complication that we should have noticed years ago if present at this frequency.…”
Section: Peter a Nigrovicmentioning
confidence: 67%
See 2 more Smart Citations
“…Intriguingly, almost 50% of patients had experienced an adverse reaction to a biologic drug, most characteristically an allergic-type reaction to tocilizumab, an otherwise quite uncommon event. These findings are echoed in the still-unpublished larger series, which includes 9 patients who were also described in the study by Schulert and colleagues, although in the larger series an extrapolated mortality of >50% at 5 years has been observed, as well as features such as lymphopenia and a striking overrepresentation of patients with trisomy 21 (8). Considering only referrals within the Cincinnati catchment area, Schulert et al provide the first estimate of the prevalence of LD in systemic JIA patients, 5 of 74 (or almost 7%), making SJIA-LD a complication that we should have noticed years ago if present at this frequency.…”
Section: Peter a Nigrovicmentioning
confidence: 67%
“…In 2013, Kimura and colleagues observed that some patients with systemic JIA developed life-threatening pulmonary complications of a kind unfamiliar to practitioners who had treated this disease for decades (7). A recent case series identified 61 additional cases (8). In this issue of Arthritis & Rheumatology, Schulert and coworkers report yet more patients matching this case description and provide the first detailed mechanistic look at systemic JIA with lung disease, designated SJIA-LD (9).…”
Section: Peter a Nigrovicmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, it resembles the inflammatory syndromes that may complicate anti-phospholipid antibody syndrome (APS), namely the catastrophic anti-phospholipid syndrome (CAPs), characterized by disseminated intravascular microthrombosis [29]; or, the systemic CLLS characterized by altered capillary wall permeability [30]. Besides CAPs and CLLS, the SARS-CoV-2 inflammation, leading to ARDS, shares pathogenic mechanisms and clinical-radiological aspects with other auto-immune/-inflammatory diseases, such as juvenile idiopathic arthritis and its adult form [31][32][33] and Kawasaki disease [34]. Systemic CLLS has also been observed in Kawasaki disease [35].…”
Section: Pathology and Laboratory Evidence Of Clls And Inflammationmentioning
confidence: 99%
“…We read with great interest the recent article by Saper et al 1 describing high mortality of systemic juvenile idiopathic arthritis (sJIA) patients affected by parenchymal lung disease (LD). LD with sJIA has also been associated with macrophage activation syndrome (MAS).…”
mentioning
confidence: 99%